Board Gender Diversity’s Moderating Effect on Capital Structure–ESG Relationship in Ghanaian Non-financial Firms - Ampomah, Philipina; Andriana, Denny; Nugraha, Nugraha; Sari, Maya (Jurnal Economia, 2025)
The study examines the relationship between capital structure and ESG (Environmental, Social, and Governance) performance of listed non-financial Ghanaian firms, emphasizing the moderating role of board gender diversity. Using panel data from 16 firms enlisted on the Ghana Stock Exchange from 2015 to 2022, the research adopts a fixed-effects model. Findings reveal that debt and equity negatively impact ESG performance, challenging traditional financial theories like Modigliani and Miller's capital structure irrelevance. Surprisingly, board gender diversity does not significantly moderate the capital structure–ESG performance link. The study underscores the need for cautious capital structure decisions to mitigate informational asymmetry costs and suggests revisiting female representation on corporate boards, given its limited influence in this context. This research advances sustainability discourse by exploring unique capital market dynamics in developing countries; in Sub-Saharan Africa and providing new insights into ESG impacts of capital structure and gender diversity in Ghanaian firms.